Narratives great and small: neighbourhood change, place and identity in Notting Hill - Martin, Graham P. (2005)
The area of Notting Hill in west London has been subject to much media coverage in recent years, which, along with substantial gentrification, has given rise to an image of the area as the epitome of fashionable London. This study investigates the views of those marginal to gentrification and mediated representation on their feelings about the local area, its image and their changing neighbourhoods. Many participants in the research resented some of the more recent changes in Notting Hill and the area's representation in the media. However, in contrast to expectations, most of the more working-class respondents involved in the research did not articulate much emotional attachment to the area. They were more concerned with what might be termed the material aspects of life in Notting Hill: convenience, facilities, safety and so on. In contrast, the more middle-class respondents frequently spoke of their regret of the changes to the area, such as the loss of independent shops, and the reduction in diversity. Paradoxically, the loss of working-class landscapes seems a relatively middle-class worry. The symbolically important landscapes described by working-class respondents were related to more immediate, material issues, in which gentrification was only a relatively minor concern.